(Eyewitness books) Ancient egypt - Hart, George (Dorling Kindersley New York, 2000)
A photo essay on ancient Egypt and the people who lived there, documented through the mummies, pottery, weapons, and other objects they left behind. Describes their society, religion, obsession with the afterlife, and methods of mummification